2010
DOI: 10.1143/jjap.49.115704
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Product after Exposing Si(111)-7×7 Surface to O2 at 300 K

Abstract: Using real-time O 1s X-ray photoelectron spectroscopy together with Si 2p X-ray photoelectron spectroscopy, the oxygen bonding configurations of oxides shortly after exposing the Si(111)-7×7 surface to O2 at 300 K are revealed. It is found that the ins structure firstly forms where one oxygen atom sits in the backbond of the silicon adatom. It is confirmed that the chemisorbed molecular oxygen, the so-called paul oxygen, is the adsorbate on top of the ins structure. It is also clarified that the ad–ins structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
54
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(62 citation statements)
references
References 71 publications
(120 reference statements)
8
54
0
Order By: Relevance
“…The component γ seems to originate from the Ge-Ge dimer at the residual unoxidized area on the surface 42 and/or can be assigned to the oxide-related component normally observed in the oxidation of Si surfaces. 25,[43][44][45] The positions of the components related to suboxide states such as Ge 1+ and Ge 2+ were set to the positions reported by Schmeisser et al 28 Figure 5 shows the results of curve-fitting analysis, and the parameters obtained from the curve-fitting analysis are shown in Table I. Our analysis clearly revealed the Ge 1+ and Ge 2+ oxidation states at core-level shifts of 0.81 and 1.71 eV, respectively.…”
Section: Resultsmentioning
confidence: 66%
See 4 more Smart Citations
“…The component γ seems to originate from the Ge-Ge dimer at the residual unoxidized area on the surface 42 and/or can be assigned to the oxide-related component normally observed in the oxidation of Si surfaces. 25,[43][44][45] The positions of the components related to suboxide states such as Ge 1+ and Ge 2+ were set to the positions reported by Schmeisser et al 28 Figure 5 shows the results of curve-fitting analysis, and the parameters obtained from the curve-fitting analysis are shown in Table I. Our analysis clearly revealed the Ge 1+ and Ge 2+ oxidation states at core-level shifts of 0.81 and 1.71 eV, respectively.…”
Section: Resultsmentioning
confidence: 66%
“…In this study, we carefully calibrated the oxygen coverage on the Ge(100) surface by referring to the results of oxygen uptake on the Si(111)-7 × 7 surface, where the relationship between the oxygen coverage and the intensity of the O 1s peak is well-understood. [25][26][27] This careful calibration allows us to assess the oxygen coverage in monolayer units (ML; 1 ML = 6.19 × 10 14 cm −2 , corresponding to the density of Ge atoms on the Ge(100)-1 × 1 surface). It was found that the final oxygen coverage was dependent on the incident energy of the oxygen, suggesting that the oxidation process can be activated by the translational energy of the O 2 molecules.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations